Ответ:
Пошаговое объяснение:
1) - 0,5m *(9n) = - 4,5mn
2) 3х + 5у - х - 9у = 2х - 4у
3) х - (х - 13) + (12 + х) = х - х + 13 + 12 + х = х + 25
4) 5 * (b + 7) - 7 * (b - 2) = 5b + 35 - 7b + 14 = -2b + 49
[tex] - 0.5m \times 9n = - 4.5mn[/tex]
[tex]3x + 5y - x - 9y = (3 - 1)x + (5 - 9)y = 2x - 4y[/tex]
[tex]x - (x - 15) + (12 + x) = x - x + 15 + 12 + x = x + 27[/tex]
[tex]5(b + 7) - 7(b - 2) = 5b + 35 - 7b + 14 = - 2b + 49[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
1) - 0,5m *(9n) = - 4,5mn
2) 3х + 5у - х - 9у = 2х - 4у
3) х - (х - 13) + (12 + х) = х - х + 13 + 12 + х = х + 25
4) 5 * (b + 7) - 7 * (b - 2) = 5b + 35 - 7b + 14 = -2b + 49
Verified answer
[tex] - 0.5m \times 9n = - 4.5mn[/tex]
[tex]3x + 5y - x - 9y = (3 - 1)x + (5 - 9)y = 2x - 4y[/tex]
[tex]x - (x - 15) + (12 + x) = x - x + 15 + 12 + x = x + 27[/tex]
[tex]5(b + 7) - 7(b - 2) = 5b + 35 - 7b + 14 = - 2b + 49[/tex]